Urinary and faecal incontinence in hospitals and nursing homes - Wójkowska-Mach, Jadwiga; Heczko, Piotr B. (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Knowledge of infection control measures in urinary and faecal incontinence population is limited. This article aimed to assess the incidence of, and potential risk factors for, common and healthcare-associated infection.